About pragmatics in translation of forms of address based on the Polish voice over and subtitles in Andrei Zvyagintsev’s drama Loveless - Mocarz-Kleindienst, Maria (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The research is rested on the thesis that the frequency of use and quality of form of address in film dialogues are subordinated to the functional parameters of the specific film genre. A qualitative and quantitative analysis was carried out of the methods of translating the nominal forms of address in the Polish voice over and subtitles Zvyagintsev’s drama Loveless. Qualitative studies have shown high tendency to transfer personal forms with morphological adaptation in both versions. Comparative and quantitative research of both Polish translations has shown a higher number of omissions in the voice over. The factor regulating the number of omissions is primarily the function of the forms of address but not asymmetry in language systems.